Repurchase Intentions in Focus: Unraveling Membership Programs, Omnichannel Strategies, and Digital Marketing Effects - Lestari, Alfina Hanni; Mitariani, Ni Wayan Eka; Hendrawan, I Gede Yudhi (Journal of International Conference Proceedings, 2023)
Customers play a vital role in business success and cannot be ignored. Since customers are the primary driver behind the founding of a firm, competitors will strive to win over new clients. Many businesses are looking for ways to retain their regular customers due to their propensity to repurchase the products the business sells. The development of lifestyle regarding facial care / skincare has resulted in many new businesses in the beauty sector, giving rise to competition between businesses. This study aims to investigate the effects of membership programs, omnichannel strategies and digital marketing on repurchase intention on Sociolla Bali. This study employs multiple linear analysis methods using SPSS 26, the findings show that (1) membership programs have a positive influence on repurchase intention; (2) omnichannel strategy has a positive effect on repurchase intention; and (3) digital marketing has a positive effect on repurchase intention. This means that the better the membership program, omnichannel strategy and digital marketing at PT. Social Bella Indonesia (Sociolla) Bali, the better the interest in repeat purchases from consumers.